INTEGRASI KONSEP AKUNTANSI BIRU DALAM SISTEM TATA KELOLA WISATA BAHARI DI PANTAI LOANG BALOQ - UTAMI, LUH; Sutriningsih (Akuntansi research UGR, 2025)
This study aims to examine the integration of blue accounting concepts in the marine tourism governance system at Loang Baloq Beach, Mataram City, West Nusa Tenggara. Blue accounting is a reporting and management approach that takes into account the economic, social and ecological values of marine resources holistically. This approach is important to apply in marine tourism management to realize environmental sustainability while supporting the welfare of coastal communities. This research used descriptive qualitative methods with data collection techniques through in-depth interviews, field observations, and documentation studies. Informants consisted of local community tourism managers. The data were thematically analyzed to identify patterns in governance practices and the potential application of blue accounting. The results showed that the tourism management system at Loang Baloq Beach still focuses on economic aspects and basic tourism services, without a reporting system on environmental and social impacts. The concept of blue accounting has not been formally applied, but there are opportunities for integration through strengthening regulations, increasing human resource capacity, and cross-sector collaboration. This research recommends the development of an environmentally inclusive reporting system that is adaptive to local conditions as a first step towards sustainable marine tourism governance.